Ability or Finances as Constraints on Entrepreneurship? Evidence from Survival Rates in a Natural Experiment - Steffen Andersen; Kasper Meisner Nielsen (Copenhagen Business School (CBS), Department of Economics, 2012)
We use a natural experiment in Denmark to test the hypothesis that aspiring entrepreneurs face financial constraints because of low entrepreneurial quality. We identify 304 constrained entrepreneurs who start a business after receiving windfall wealth and examine the performance of these marginal entrepreneurs. We find that constrained entrepreneurs have significantly lower survival rates and lower profits when compared with a matched sample of unconstrained entrepreneurs. These results are consistent with the hypothesis that the marginal entrepreneur is of low quality
hdl:10398/8499
Keywords: L26; 330; entrepreneurship; natural experiments